Emergency medical services : clinical practice and systems oversight - Cone, David C.; Brice, Jane H.; Delbridge, Theodore R.; Myers, J. Brent (John Wiley & Sons Inc., 2015)
Emergency Medical Services: Clinical Practice and Systems Oversight is the official textbook of the National Association of EMS PhysiciansTM (NAEMSPTM) National EMS Medical Directors Course and PracticumTM. Now paired with a companion website featuring self-assessment exercises, audio and video clips of EMS best practices in action, and more, this essential study aid guides students through the core knowledge they need to successfully complete their training and begin their careers as EMS physicians.